A Comprehensive Case Report on Tuberculosis Meningitis: A Nurse’s Perspective on Diagnosis, Management, and Patient Care - Ms. Vaishnavi Dongare (European Journal of Case Reports and Clinical Images, 2025)
The organism that causes tuberculosis is called Mycobacterium TB. The germs can spread to other organs and tissues through the circulation if the illness is not treated immediately. Tubercular meningitis will result from the infection's progression to the meninges, where it will inflame the membranes. A 42-year-old male patient with tuberculous meningitis is the subject of this investigation. The patient's chief complaints are a low-grade fever and chills that have persisted for a month, a five- to six-day-old frontal headache, altered sensorium, breathing issues, diminished speech, and a one-day-old left-side weakness. He had a battery of testing upon admission to the ward, including blood work, lumbar punctures, electrocardiograms, and brain MRIs. Eventually, tuberculous meningitis was the diagnosis. After being admitted to the intensive care unit at Hospital, the patient was placed on nasogastric tube support, a Foley catheter, and NIV support after undergoing examinations. The catheter was removed when the patient's condition improved, and they were moved to a ward. Injections of Ctri 2 gm, levoflox 500 mg, thiamine 100 mg, injections of dexamethasone 10 mg, tabs of Pan 40 mg, tabs of Akt4 3, injections of mannitol, and tabs of lorazepam were the methods of patient medical therapy in the ward. Following the completion of all therapies and improvements in the patient's condition, a nursing care plan, physical examination, neurological evaluation, and obtaining a patient's history were finished. Keywords: Scrofula brain fever, Tubercle bacillus, Treatment, Nursing management, tuberculous meningitis. References: 1. https://www.ncbi.nlm.nih.gov/pmc/articles /PMC4121465 / 2. https://www.ncbi.nlm.nih.gov/pmc/articles /PMC164219/ 3. https://www.ncbi.nlm.nih.gov/pmc/articles /PMC4347078/ 4. https://www.who.int/news-room/factsheets/detail/tuberculosis 5. https://www.nzbri.org/resources/publicatio ns/185/Anderson_Journal-of-ClinicalNeuroscience_2010.pdf 6. https://www.ncbi.nlm.nih.gov/pmc/articles /PMC4121465/ 7. https://bmcpulmmed.biomedcentral.com/a rticles/10.1186/s12890-019-0966-8